The Expression of Transcription Factors Mecp2 and CREB Is Modulated in Inflammatory Pelvic Pain - Xie, Alison Xiaoqiao; Pan, Xiao-Qing; Meacham, Randall B.; Malykhina, Anna P. (Frontiers in Systems Neuroscience, 2019)
Early activation of transcription factors is one of the epigenetic mechanisms contributing to the induction and maintenance of chronic pain states. Previous studies identified the changes in a number of nociception-related genes, such as calcitonin gene-related peptide (CGRP), substance P (SP), and brain-derived neurotropic factor (BDNF) in the pelvic organs after transient colonic inflammation. The gene and protein expression of these neuropeptides could be modulated by transcription factors Methyl-CpG-binding protein 2 (Mecp2) and cAMP response element-binding protein (CREB). In this study, we aimed to evaluate time-dependent changes in the expression levels of Mecp2 and CREB in the lumbosacral (LS) spinal cord and sensory ganglia after inflammation-induced pelvic pain in rat. Adult Sprague Dawley rats were treated with 2,4,6-trinitrobenzenesulfonic acid (TNBS) to induce transient colonic inflammation. Lumbosacral (L6-S2) spinal cord segments and respective dorsal root ganglia (DRGs) were isolated from control and experimental animals at 1, 2, 6, 24 hours and 3 days post-TNBS treatment. Immunohistochemical (IHC) labeling and Western blotting experiments were performed to assess the expression of Mecp2, CREB and their phosphorylated forms. Total Mecp2 expression, but not phosphorylated p- Mecp2 (pS421Mecp2) expression was detected in the cells of the spinal dorsal horn under control conditions. Colonic inflammation triggered a significant decrease in the number of Mecp2-expressing neurons in parallel with elevated numbers of pS421Mecp2-expressing cells at 2 hours and 6 hour post-TNBS. The majority of Mecp2-positive cells (80±6%) co-expressed CREB. TNBS treatment caused a transient up-regulation of CREB-expressing cells at 1h post-TNBS only. The number of cells expressing phosphorylated CREB (pS133CREB) did not change at 1 hour and 2 hours post-TNBS, but was down-regulated by 3 folds at 6 hours post-TNBS. Analysis of DRG sections revealed that the number of Mecp2-positive neurons was up-regulated by TNBS treatment, reaching 3-fold increase at 2 hours post-TNBS, and 8-fold increase at 6 hours post-TNBS (p≤0.05 to control). These data showed early changes in Mecp2 and CREB expression in the dorsal horn of the spinal cord and sensory ganglia after colonic inflammation, suggesting a possible contribution Mecp2 and CREB signaling in the development of visceral hyperalgesia and pelvic pain following peripheral inflammation.